2006
DOI: 10.1111/j.1365-2362.2006.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased coronary sinus blood temperature: correlation with systemic inflammation

Abstract: Systemic inflammation is well correlated with CS temperature; thus, an inflammatory process could be the underlying mechanism for increased heat production from the myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
(26 reference statements)
0
8
0
1
Order By: Relevance
“…Similarly, elevated levels of IL-6 not only in the CS, but also in the aorta were also reported in ACS patients [18], while translesional CRP gradient (distal CRP minus proximal CRP) as well as the proximal CRP and distal CRP was higher in unstable angina than in stable angina [19]. In this field Toutouzas et al [20] demonstrated that systemic inflammation is well correlated with CS temperature; thus, an inflammatory process could be the underlying mechanism for increased heat production from the myocardium. However, the same group [21] showed later that heat production from the myocardium, as estimated from the CS blood temperature, was not correlated with inflammatory process.…”
Section: Atheromatous Plaque and Crp Productionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similarly, elevated levels of IL-6 not only in the CS, but also in the aorta were also reported in ACS patients [18], while translesional CRP gradient (distal CRP minus proximal CRP) as well as the proximal CRP and distal CRP was higher in unstable angina than in stable angina [19]. In this field Toutouzas et al [20] demonstrated that systemic inflammation is well correlated with CS temperature; thus, an inflammatory process could be the underlying mechanism for increased heat production from the myocardium. However, the same group [21] showed later that heat production from the myocardium, as estimated from the CS blood temperature, was not correlated with inflammatory process.…”
Section: Atheromatous Plaque and Crp Productionmentioning
confidence: 72%
“…• Decreases eNOS expression [8] • Decreases cGMP [8] • Increases monocyte adhesion to aortic endothelium [8] • Increases CS temperature [20] • Interacts with apoB-containing particles [26] • Increases the activation of p38 kinase [30] • Activation of endothelial cells [34] • Increases the expression of NADH/NADPH oxidase p22 phox protein [35] • Increases the generation of ROS in cultured human CASMCs [35] • Induces the expression of GTPCH-1 [36] Abbreviations. eNOS: endothelial nitric oxide synthase; cGMP: cyclic guanosine monophosphate; CS: coronary sinus; CASMCs: coronary artery smooth muscle cells; GTPCH-1: guanosine triphosphate cyclohydrolase 1; ROS: reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated CS temperature reflects the inflammatory activation in the myocardium, as has been shown in previous studies. In patients with acute coronary syndromes CS temperature was increased and correlated with the levels of CRP in the peripheral blood [17,18]. On the contrary, systemic inflammatory activation was not related to CS temperature in patients with end-stage dilated cardiomyopathy [16].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the systemic inflammatory activation in patients with AF may be depicted by increased heat production from the myocardium. The transfer of a proportion of the excess heat through coronary circulation may result in increased CS temperature compared to right atrial (RA) temperature [17,18]. The purpose of our study was to investigate whether in patients with AF 1) there is increased CS blood temperature, and 2) the systemic inflammatory activation, evaluated by the levels of CRP, is correlated with CS temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Though patients with ACS had greater temperature difference compared to patients with SA, the difference did not reach statistical significance. The levels of C-reactive protein (CRP) were well correlated with temperature [32]. Temperature differences were higher in patients with angiographically significant lesions, independently of the site of the lesion, compared to subjects without coronary artery disease.…”
Section: Human In Vivo Intracoronary Thermography Studiesmentioning
confidence: 99%